Blue Economy Legal Codification of Malaysian Social Finance: Harmonizing Law and Fiqh in Maritime - Harahap, Tuan Afero; Hamid, M. Arfin; Librayanto, Romi; Saputra, Muhammad Nurul Dzaki; Mursyid, Besse Tenriabeng (Universitas Islam Negeri Alauddin Makassar, 2026)
The persistent disparity between Indonesia’s abundant maritime resources and the economic precarity of coastal communities reveals a structural gap within the existing legal framework. This article examines the Blue Economy framework through the lens of Maqāṣid al-Sharīʿah, aiming to shift the discourse from general development ethics toward more precise Islamic legal reasoning (istinbāṭ). Employing normative legal research with statutory and comparative approaches, particularly through an examination of the legal codification of Islamic social finance in Malaysia, this study analyzes the harmonization between positive maritime law and fiqh principles. The research demonstrates a legal novelty by revealing that current regulatory models have failed to fulfill the imperative of ḥifẓ al-māl (the preservation of wealth) for small-scale fishers. It proposes a juridical reconstruction in which equity-based contracts (muḍārabah and mushārakah) and ZISWAF instruments are integrated not merely as voluntary alternatives but as binding statutory obligations. The findings indicate that the institutionalization of these fiqh-based mechanisms establishes a robust legal safety net capable of effectively addressing structural poverty. Accordingly, this study contributes to the development of fiqh siyāsah (Islamic political jurisprudence) and Islamic economic law by formulating a justiciable governance model. It concludes that the synthesis of Maqāṣid methodology and positive law provides a definitive legal pathway toward sustainable coastal welfare while aligning economic development with the principles of Sharīʿah.